Analytic hierarchy process for assessing sustainability of bazaars: The case of Tajrish bazaar in Tehran - Nejadriahi, Halleh; Fasli, Mukaddes (Palgrave Macmillan Ltd, 2017)
Throughout history, shopping and social interaction in bazaars had been among the most important traditions in the lifestyle of Iranian people. Owing to this fact, the continued sustainability of Bazaars needs to be ensured. This article adopts Analytic hierarchy process (AHP), as a multi-criteria decision making method, for assessing the sustainability of the Tajrish Bazaar in the capital city of Iran; Tehran. In this study, an examination of the environmental, social and economic dimensions of sustainability in the Tajrish Bazaar reveals that the social dimension is the most sustainable one, followed by the economic and environmental dimensions respectively. As research for assessing sustainability of bazaars in a systematic way is rare, this article offers a significant contribution through the use of AHP method.
Keywords: AHP; MCDM; sustainability; bazaar; Tehran